Fibroblast Growth Factor 21 (FGF21) Protects against High Fat Diet Induced Inflammation and Islet Hyperplasia in Pancreas. - Garima Singhal (PLoS ONE, 2016)
Fibroblast growth factor 21 (FGF21) is an important endocrine metabolic regulator expressed in multiple tissues including liver and adipose tissue. Although highest levels of expression are in pancreas, little is known about the function of FGF21 in this tissue. In order to understand the physiology of FGF21 in the pancreas, we analyzed its expression and regulation in both acinar and islet tissues. We found that acinar tissue express 20-fold higher levels than that observed in islets. We also observed that pancreatic FGF21 is nutritionally regulated; a marked reduction in FGF21 expression was noted with fasting while obesity is associated with 3-4 fold higher expression. Acinar and islet cells are targets of FGF21, which when systemically administered, leads to phosphorylation of the downstream target ERK 1/2 in about half of acinar cells and a small subset of islet cells. Chronic, systemic FGF21 infusion down-regulates its own expression in the pancreas. Mice lacking FGF21 develop significant islet hyperplasia and periductal lymphocytic inflammation when fed with a high fat obesogenic diet. Inflammatory infiltrates consist of TCRb+ Thy1+ T lymphocytes with increased levels of Foxp3+ regulatory T cells. Increased levels of inflammatory cells were coupled with elevated expression of cytokines such as TNFα, IFNγ and IL1β. We conclude that FGF21 acts to limit islet hyperplasia and may also prevent pancreatic inflammation.